The Medical Community's Evolving Focus on Physician and Surgeon Pregnancy: Thematic Trends From a Scoping Review. (23rd June 2022) - Hanchuk, Stephanie; Casilla-Lennon, Marianne; Zheng, Sijin; Kim, David D.; Press, Benjamin; Nguyen, Justin V.; Grimshaw, Alyssa; Leapman, Michael S.; Rickey, Leslie M.; Cavallo, Jaime A.
Abstract : Purpose: The authors aimed to chronicle the evolution of the medical community's study of physician and surgeon pregnancy by investigating thematic trends in the literature in the context of pertinent sociopolitical events. Method: A scoping review was conducted in Cochrane Library, Google Scholar, Ovid MEDLINE, Ovid Embase, Scopus, and Web of Science Core Collection from inception through August 11, 2020, using vocabulary and terms for physicians (including surgeons), pregnancy, and family leave. Study populations were categorized by all physician specialties or exclusively surgical specialties as well as by all career levels or exclusively trainees. Subthemes and themes were based on a priori assumptions of physician pregnancy and extrapolated from previously published reviews, respectively. Thematic trends were analyzed by plotting the total number of publications and the frequency of themes and subthemes by publication year. Results: After title and abstract and full-text reviews, 407 manuscripts met inclusion criteria. Publications on physician pregnancy first emerged in the 1960s and surged from 1988 to 1996 and again from 2010 to 2019. The first known manuscript exclusively on surgeon pregnancy was published in 1991; subsequent publication frequency trends for surgeon pregnancy generally paralleled those for all physician pregnancy publications albeit in reduced quantities. Four major themes were found: impact of pregnancy on the physician and her colleagues, pregnant physician work productivity, physician maternity leave policies, and physician maternal–fetal health outcomes. Conclusions: As the number of women physicians increased and the sociopolitical environment progressed, the thematic focus of the literature on physician pregnancy evolved. Multi-institutional prospective observational studies are needed to develop definitive evidence-based recommendations that will positively impact physician pregnancy.